The ECB's 2019 Liquidity Stress Test: An Event Study Evaluating the Impact on Owners and Creditors - Christoph J. Börner; Jonas Krettek (Credit and Capital Markets – Kredit und Kapital, 2021)
The liquidity stress test (LiST) 2019 by the European Central Bank (ECB) examines the liquidity situation of banks, which is novel at the European level. Therefore, a well-founded empirical analysis is necessary to derive implications for the capital market. This paper investigates the impact on stock returns and credit default swap (CDS) spread changes of the participating banks using an event study methodology. This approach allows for conclusions about the entire capital market. A major problem with the sample, event clustering, is addressed with appropriate test statistics. The paper provides evidence of the absence of a capital market reaction, which could be the goal of supervisors, namely, being able to assess the banking sector and providing general information without triggering panic.
Keywords: G01; G14; G28; 330; Liquidity Stress Test 2019; Liquidity Risk; Event Study; ECB Stress Testing; European Banking Sector